Google classroom as an alternative media of reading logs in a reading course - Laksmi Widyarini; Afria Dian Prastanti (Journal of English Language and Pedagogy, 2020)
This research generally aims to identify the reading skills and interest of the semester 1 students of the English Department, Universitas Sarjanawiyata Tamansiswa. The specific objective of the research is to formulate a procedure for using Google classroom as an alternative media for reading logs in reading subjects. The reading subject is chosen because reading is a compulsory subject and a prerequisite for the following courses. This research applied a descriptive-qualitative approach. Data collection was carried out using observation, questionnaires, and interviews. The research began with data collection regarding the students’ reading skills, interest, as well as the relevant facilities in the google classroom as reading logs in the reading subject. The data collected were then analyzed, linked, and developed according to the lecture activities in the reading subject. Interviews were conducted to strengthen and complement findings on how google classroom could be used as an alternative media for reading logs in reading subjects.